2015
DOI: 10.1155/2015/689306
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Improvement under Visible Light in TiO2 Nanoparticles by Carbon Nanotube Incorporation

Abstract: Photocatalytic activity of TiO 2 nanoparticles was successfully enhanced by addition of multiwall carbon nanotubes (MWCNT) to make CNT/TiO 2 nanocomposites by sol-gel method at ambient temperature. CNT treated by HNO 3 : H 2 SO 4 treatment (1 : 3 v/v) was mixed with TiO 2 nanoparticles at various molar ratios and calcination temperatures. The optimal molar ratio of CNT : TiO 2 was found at 0.05 : 1 by weight. The optimal calcination condition was 400 ∘ C for 3 h. From the results, the photocatalytic activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…44 Further, the FT-IR spectrum of the FMWCNTs showed the peaks of carboxyl (C]O) and carbonyl (O-C]O) groups at z1650 cm À1 and z1450 cm À1 , respectively. 44,55,56 Thus, these peaks from the FT-IR indicated the presence of functional groups on the surface of FMWCNTs aer covalent acid functionalization.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 98%
“…44 Further, the FT-IR spectrum of the FMWCNTs showed the peaks of carboxyl (C]O) and carbonyl (O-C]O) groups at z1650 cm À1 and z1450 cm À1 , respectively. 44,55,56 Thus, these peaks from the FT-IR indicated the presence of functional groups on the surface of FMWCNTs aer covalent acid functionalization.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 98%
“…It was also observed a broad peak from OH group in the carboxylic acid group at 3,453 cm −1 . It can be confirmed that chemical modification of MWCNT was successfully carried out using acid mixture [31,[34][35][36][37][38].…”
Section: Ftir Analysismentioning
confidence: 70%
“…A pretreatment was applied to commercial MWCNT prior to use in the preparation of composite membranes. For this purpose, MWCNT was functionalized with negatively charged carboxyl ( COOH) group as explained in the literature [7,31]. After modification of MWCNT's surface, it was expected that MWCNT can disperse very efficiently in negatively charged PAA for LbL assembly.…”
Section: Functionalization Of Mwcnt and Preparation Of The Composite mentioning
confidence: 99%
“…Soroodan and Fatemi synthesized TiO2/ CNTs composites using sol-gel method for the degradation of acetaldehyde. Benzyl alcohol as the linking agent was added to the TiO2/ CNTs composites resulting in homogeneously coating of TiO2 sols over the CNTs [52][53][54].…”
Section: Sol-gelmentioning
confidence: 99%